The legal position of a foundation in agricultural law regulations - Litwiniuk, Przemysław; Litwiniuk, Edyta (Przegląd Prawa Rolnego, 2024)
The aim of this article is to present the origins and contemporary legal position of a foundation under Polish law and to confront it with the concept of entities falling within the scope of the agricultural system as expressed in Polish agricultural legislation. In particular, the usefulness of the institution of a foundation and a family foundation as a legal form of running family farms has been analysed. The value of this type of formula was considered to be the legal nature of a foundation as being conducive to more effective management and protection of the sustainability of agricultural production units against their division in the process of succession, which may also provide them with greater economic security. The dysfunctions of the current agricultural law regulations which excessively interfere with the freedom of establishment and operation of foundations (Article 12 of the Constitution of the Republic of Poland) and the constitutional guarantees of the protection of property and other property rights as well as the freedom of economic activity have been presented. The authors postulate an appropriate adjustment of the legal solutions covered by the provisions of the Act on shaping of the agricultural system to the patterns derived from the Constitution of the Republic of Poland.